Multistate model in the behavioral study of the parasitoid Telenomus podisi for biological soybean control - Torres de Paula, Laura Vicuña; Antonio Rodrigues de Lara, Idemauro; Reigada, Carolina; José Bon, Victor (Brazilian Journal of Biometrics, 2023)
Biological pest control through the use of wasps are sustainable ways of protecting plants and, consequently, agricultural production. In this context, an entomological experiment is motivated, in which the forraging and reproductive behaviors of the parasitoid Telenomus podisi were qualified over time, considering non parasitized (sp0) and parasitized (sp1) of the brown stink bug, Euschistus heros. The experiment features a longitudinal study of continuous time with variable nominal qualitative response, grouped into four mutually exclusive categories (flying-walking, drumming, oviposition and marking). Continuous time transition models, also known as multistate models, are a viable alternative for analyzing data with these characteristics. Therefore, this class of models was considered in this work to study the behavior of the parasitoid, through the average length of stay in each of the response categories, as well as their preference probabilities. As a result, there was a significant effect of the treatment of host eggs (non parasitized or previously parasitized). When having contact with previously parasitized eggs, the female parasitoid T. podisi has preference for the categories of movement which are flying-walking and drumming. In contrast, when in contact with non parasitized eggs, the female T. podisi has a preference for oviposition and marking. The applied methodology proved to be adequate for this typical experimental situation in entomological studies associated with the description of the behavior of a parasitoid.